2022
DOI: 10.1155/2022/8221706
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Supply Chain Management Modules Enabling Advanced Manufacturing for the Electric‐Mechanical Equipment Industry

Abstract: Electric-mechanical equipment manufacturing industries focus on the implementation of intelligent manufacturing systems in order to enhance customer services for highly customized machines with high-profit margins such as electric power transformers. Intelligent manufacturing consists in using supply chain data that are integrated for smart decision making during the production life cycle. This research, in cooperation with a large electric power transformer manufacturer, provides an overview of critical intel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Gao [19] study found that cellulose molecules in the process of pyrolysis rst decomposition into cellulose monomer, then cellulose monomer hydroxyl functional group priority removal, the intermediate product of liquid products, so paper reforming volatile will contain a large number of hydroxyl functional group, nally after reforming the liquid, oxygenation content is still relatively high. ese ndings in this article have potential application prospects in the manufacturing industry [20][21][22][23][24][25][26][27].…”
Section: Fractions Of the Reforming Fluidmentioning
confidence: 79%
“…Gao [19] study found that cellulose molecules in the process of pyrolysis rst decomposition into cellulose monomer, then cellulose monomer hydroxyl functional group priority removal, the intermediate product of liquid products, so paper reforming volatile will contain a large number of hydroxyl functional group, nally after reforming the liquid, oxygenation content is still relatively high. ese ndings in this article have potential application prospects in the manufacturing industry [20][21][22][23][24][25][26][27].…”
Section: Fractions Of the Reforming Fluidmentioning
confidence: 79%
“…Wang, Y. et al [12] through a case study based on four Chinese cross-border e-commerce enterprises, found that cross-border e-commerce companies laterally enhance the core competitiveness of the enterprise and at the same time, achieve high social benefits. Cross-border e-commerce as a synergistic development of the industry, and the supply chain link requirements are higher [13][14]. Xu, Y [15] believes that it can set up supply chain information security and other aspects of the supply chain to establish information supply chain partnerships, to improve economic efficiency, and ultimately, to provide a modern service industry with faster growth assurance.…”
Section: Introductionmentioning
confidence: 99%
“…Machine Learning (ML) and Artificial Intelligence (AI) can offer exciting new possibilities for manufacturing CPS [6]. A model can predict the quality of finished products using Auto-Regressive Integrated Moving Average (ARIMA), which is machine learning [7]. A recent study has proven that Long Short-Term Memory (LSTM) is suitable for predicting inventory supply and demand in the manufacturing process [8].…”
Section: Introductionmentioning
confidence: 99%